The complete encyclopedia minerals - Korbel, Petr, 1961- (Lisse : Rebo Publishers, 2005)
'The Complete Encyclopedia of Minerals' offers a fascinating glimpse into the beautiful world of minerals. It contains hundreds of photographs of beautiful crystals and crystal aggregates, together with a list of well-known and new discoveries of deposits for each type of mineral. The minerals are arranged into sections based on the standard classification system: Elements, Sulfides, Halides, Oxides, Carbonates etc...
1